Incidence and demographic determinants of lymphocytic leukemia in pediatric patients with cancer, Antioquia - Gómez-Mercado, Carlos A.; Segura-Cardona, Angela M.; Pájaro-Cantillo, Dubán Enrique; Mesa-Largo, Miler (Universidad y Salud, 2020)
Introduction: Acute leukemias are the most frequent pediatric malignancies worldwide that have led to a great interest due to their implications for children and their families. Objective: To identify the incidence of acute lymphocytic leukemia and its association with demographic determinants in pediatric cancer patients from Antioquia (Colombia) in 2017. Materials and methods: An observational, descriptive, cross-sectional, retrospective study was carried out with an analytical approach to identify the incidence of acute lymphocytic leukemia (ALL) and its association with non-causal demographic determinants in patients with pediatric cancer. 190 records from the Public Health Surveillance System (SIVIGILA) were analyzed. Results: The incidence rates of childhood cancer and ALL were 10 and 4 cases per 100,000 inhabitants ≤18 years of age, respectively. The variables associated with ALL are: being male (APR: 1.02 95% CI: 0.52 – 2.02); living in rural areas (APR: 1.59 95% CI: 0.55 – 4.56); being affiliated to the subsidized regime (APR: 1.41 95% CI: 0.68 – 2.92); being ≥ 9 years of age (APR: 0.76 95% CI: 0.38 – 1.50); and having a confirmatory diagnosis after 16 days (APR: 0.34 95% CI: 0.10 – 1.15). Conclusions: The variables related to acute lymphocytic leukemia are: being a man; living in rural areas; and being affiliated to the subsidized regime.